An Analysis of Paraphrasing Techniques Used by Student at the Fifth Grade English Education Department of IAIN Bukittinggi Academic Year 2022/2023 - Zohra, Meilanie; Melani, Melyann; Roza, Veni; Prima Dewi, Merry (Yayasan Lembaga Studi Makwa, 2022)
This research was conducted based on the problem found in academic writing class about paraphrasing at English Education Department at the fifth semester IAIN Bukittinggi. Paraphrasing is known as a way to avoid plagiarism while creating scientific papers or journals. However, the researcher interviewed the lecturer and found that the most of the students have difficulty putting the ideas into their own words. They used too many words from the original passage that shows the students were lack of vocabulary mastery. Moreover, the students used monotonous technique of paraphrase. This research used mixed method. It is a procedure for collecting, analyzing, and mixing both quantitative and qualitative methods in a single study or a series to understand a research problem. The students were given a paraphrasing test to know the students ability. The data were analyzed using scoring rubric proposed by Callison. After that, some students were interviewed to find out the dominant paraphrasing technique used by the students. After calculating the score, the result of the study showed that the student’s ability in paraphrasing was 59. As writing band suggested by Leo, the students’ ability in paraphrasing is in moderate level where it is rather well organized. Arguments are rather relevant in relation to writer’s view. Main ideas and supporting ideas are rather clear. The message is almost clear but with some loss of detail. In addition, the interview showed that most of the students use synonym replacement technique in paraphrasing the text. It is because most of the student agreed that the technique is the easiest technique to use.